Sports Nutrition - Current Recommendations - Carlsohn A; Braun H; Großhauser M; König D; Lampen A; Mosler S; Nieß A; Oberritter H; Schäbethal K; Schek A; Stehle P; Virmani K; et al. (Deutsche Zeitschrift für Sportmedizin)
An adequate intake of minerals and vitamins is essential for health and performance of athletes. Depending on the type of sport and the intensity and scope of physical performance, as well as individual factors (such as dietary behavior, perspiration rate and composition of perspiration), athletes may be at increased risk of suboptimal micronutrient supply.This position paper will provide an overview of the potential causes of deficient micronutrient supply in athletes, such as increased requirements as a result of enhanced energy metabolism, higher losses associated with physical activity, and special diets associated with sport in general or particular types of sport. This position statement will also present the proven effects of insufficient micronutrient supply on the health and performance of athletes, and the effects on their supply situation.In summary, it can be concluded that with a balanced diet that covers energy requirements, the D-A-CH reference values for micronutrients can usually be attained without any problems. However, in certain situations (such as strenuous endurance exercise or weight reduction, or in the case of lopsided eating habits or hypocaloric diets), iron, calcium, sodium and vitamin D may be critical nutrients for athletes.A diet that is adapted to the individual and covers all requirements is achievable even in the case of high metabolic demands, and such a diet can reduce the risk of nutrient deficiencies. Key Words: Micronutrients, Requirements of Athletes, Health, Exercise Performance